Antioxidant-Activity and Physicochemical Indices of the Rice Beer Used by the Bodo Community in North-East India. (3rd April 2018) - Deka, Anamika Kalita; Handique, Pranami; Deka, Dibakar Chandra
ABSTRACT: Rice beer Jou is used by the Bodo community of North-East India for their livelihood. Joubidwi (JB, fresh rice beer), Joufinai (JF, stored rice beer), and Jougwran (JG, distilled rice beer) are the three varieties of Jou prepared by Bodos through the process of fermentation of rice with a locally prepared starter culture Amao . Herein, antioxidant activities and physicochemical characteristics such as color, bitterness, pH, alcohol content, protein content, and carbohydrate content of all types of Jou have been reported. Beer color (2.58 ± 0.18 to 78.05 ± 0.21 European Brewing Convention [EBC]), bitterness (3.71 ± 0.08 to 21.34 ± 0.23 European Bitterness Unit [EBU]), pH value (3.75 ± 0.25 to 4.32 ± 0.03), ethanol content (43.42 ± 0.57 to 127.85 ±2.06 mg/mL), and protein content (0.35 ± 0.01 to 0.79 ± 0.06 mg bovine serum albumin equivalents (BSAE)/mL) are gradually increased from fresh JB to 15 month old JF. Antioxidant activity (0.86 ± 0.04 to 2.20 ± 0.02 mg/mL in ascorbic acid equivalents [ASAE]), polyphenol (2.63± 0.00 to 4.18± 0.00 mg/mL in gallic acid equivalents), and flavonoid content (10.04 ± 0.29 to 28.95 ± 1.71 mg/mL in quercetin equivalents [QAE]) are also increased gradually with the storage period. A negative correlation of carbohydrate content with storage is observed. JG with 332.92 ± 2.55 mg /mL ethanol is the highest ethanol containing beverage among the three types of Jou .